2021
DOI: 10.34238/tnu-jst.4107
|View full text |Cite
|
Sign up to set email alerts
|

Ielts Reading Test-Taking Strategies Employed by High Score Candidates in Academic Training Module

Abstract: Nghiên cứu này nhằm mục đích làm sáng tỏ những chiến thuật đọc thường được áp dụng bởi những thí sinh đạt điểm cao kỹ năng đọc trong bài thi IELTS học thuật. Hai câu hỏi nghiên cứu gồm: (1) Các thí sinh Việt Nam thường sử dụng chiến lược làm bài nào trong các bài thi đọc IELTS? (2) Các chiến lược làm bài thi đó có liên quan như thế nào đến thành tích của thí sinh? Nghiên cứu sử dụng phương pháp khảo sát đối với 100 người tham gia và phỏng vấn 06 người học tiếng Anh đã tham gia kỳ thi IELTS và đạt ít nhất 7.0 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Sharing similar findings with the results of the study by Phi and Vu (2021), the current study identified the strategies that were most frequently employed by Vietnamese students. These strategies included those that involved guessing meaning in contexts to facilitate comprehension, and those that helped locate important information for answering questions.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Sharing similar findings with the results of the study by Phi and Vu (2021), the current study identified the strategies that were most frequently employed by Vietnamese students. These strategies included those that involved guessing meaning in contexts to facilitate comprehension, and those that helped locate important information for answering questions.…”
Section: Discussionsupporting
confidence: 87%
“…In another study, Phi and Vu (2021) investigated the test-taking strategies used by high scorers in IELTS reading tests and how these strategies correlated with test performance. The study included 100 students who reported on their employment of strategies through a questionnaire and a limited number of interviews (N = 6).…”
Section: Relevant Studies In Vietnammentioning
confidence: 99%
See 2 more Smart Citations